Financial Distress, ESG Disclosure, and Tax Avoidance: The Moderating Role of Audit Quality in Post-Pandemic Non-Cyclical Consumer Firms - Sofiyatur Rohmah; Novi Darmayanti; Isnaini Anniswati Rosyida (Politeknik Ganesha Medan, 2026)
This study aims to examine the influence of financial difficulties and Environmental, Social, and Governance (ESG) disclosures on tax avoidance practices, with audit quality as a moderating variable. This research addresses gaps in the literature, as previous studies have produced inconsistent findings regarding the role of ESG and financial difficulties in influencing tax avoidance, especially in post-pandemic defensive sectors. This study adopts a quantitative approach using secondary data. The population consists of non-cyclical consumer sector companies listed on the Indonesia Stock Exchange during the period 2020–2024. Using purposive sampling, 21 companies were selected, resulting in 105 observations over the five-year period. Data were obtained from annual financial statements and sustainability reports published on the company's website and the Indonesia Stock Exchange. Panel data regression analysis was used, with EViews 13 employed for data processing. The findings indicate that neither financial difficulties nor ESG disclosures have a significant impact on tax avoidance. Furthermore, audit quality does not moderate the relationship between financial difficulties, ESG disclosures, and tax avoidance. These results highlight that tax avoidance behavior in post-pandemic non-cyclical consumer companies tends to be stable and is not significantly influenced by company-level financial pressures or ESG practices, nor is it reinforced by external monitoring thru audit quality. The findings indicate that tax avoidance in the defensive sector is driven structurally rather than influenced by corporate-level governance mechanisms.